Discovery of fevipiprant (NVP-QAW039), a potent and selective DP2 receptor antagonist for treatment of asthma - Sandham, David A.; Barker, Lucy; Brown, Lyndon; Brown, Zarin; Budd, David; Charlton, Steven J.; Chatterjee, Devnanden; Cox, Brian; Dubois, Gerald; Duggan, Nicholas; Hall, Edward; Hatto, Julia; et al. (American Chemical Society, 2017)
Further optimization of an initial DP2 receptor antagonist clinical candidate NVPQAV680 led to the discovery of a follow-up molecule 2-(2-methyl-1-(4-(methylsulfonyl)-2- (trifluoromethyl)benzyl)-1H-pyrrolo[2,3-b]pyridin-3-yl)acetic acid (compound 11, NVP-QAW039, fevipiprant), which exhibits improved potency on human eosinophils and Th2 cells, together with a longer receptor residence time, and is currently in clinical trials for severe asthma.